2011
DOI: 10.1016/j.biocel.2011.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin 1 is more dependent on the P proteins of the ribosomal stalk for depurination activity than Shiga toxin 2

Abstract: Shiga toxins produced by E. coli O157:H7 are responsible for food poisoning and hemolytic uremic syndrome (HUS). The A subunits of Shiga toxins (Stx1A and Stx2A) inhibit translation by depurinating a specific adenine in the large rRNA. To determine if Stx1A and Stx2A require the ribosomal stalk for depurination, their activity and cytotoxicity were examined in the yeast P protein deletion mutants. Stx1A and Stx2A were less toxic and depurinated ribosomes less in a strain lacking P1/P2 on the ribosome and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 49 publications
0
63
0
Order By: Relevance
“…The depurination activity of Stx1A on the ribosome was greatly reduced if P1/P2 binding sites on P0 were deleted, while the depurination activity of Stx2A was not affected as much, indicating that although stalk P-proteins were important for ribosome depurination by both toxins, Stx2A was less dependent on the stalk proteins for depurination of the SRL than Stx1A (25). We recently showed that Stx2A1 has a higher affinity for the ribosome and higher catalytic activity and toxicity than Stx1A1 in both yeast and mammalian cells (26).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The depurination activity of Stx1A on the ribosome was greatly reduced if P1/P2 binding sites on P0 were deleted, while the depurination activity of Stx2A was not affected as much, indicating that although stalk P-proteins were important for ribosome depurination by both toxins, Stx2A was less dependent on the stalk proteins for depurination of the SRL than Stx1A (25). We recently showed that Stx2A1 has a higher affinity for the ribosome and higher catalytic activity and toxicity than Stx1A1 in both yeast and mammalian cells (26).…”
mentioning
confidence: 93%
“…We previously showed that the ribosomal P-protein stalk is required for ribosome depurination and toxicity of the A subunits of Stx1 and Stx2 (25). The depurination activity of Stx1A on the ribosome was greatly reduced if P1/P2 binding sites on P0 were deleted, while the depurination activity of Stx2A was not affected as much, indicating that although stalk P-proteins were important for ribosome depurination by both toxins, Stx2A was less dependent on the stalk proteins for depurination of the SRL than Stx1A (25).…”
mentioning
confidence: 99%
“…RNA was purified (43), and the depurination of rRNA was quantified by using a qRT-PCR assay (42). The ⌬⌬C T method was used to calculate the depurination level, and data were expressed as the fold change of depurination in Stx-treated RNA over depurination in nontreated RNA, as described previously (40,42).…”
Section: Methodsmentioning
confidence: 99%
“…Monomeric ribosomes were isolated from W303 cells as described previously (40), with the following modifications. The cell-free supernatant was incubated with 1% Triton X-100 for 30 min at 4°C with gentle shaking to increase the ribosome yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation